Examining Malaysian public letters to editor on COVID-19 pandemic: a corpus-assisted discourse analysis - Siti Aeisha Joharry; Syamimi Turiman (Penerbit Universiti Kebangsaan Malaysia, 2020)
Around the world, people are now facing an unprecedented situation with the COVID-19 virus pandemic. With numerous countries announcing various modes of self-quarantine and social distancing, the Malaysian government has initially called for a 3-week Movement Control Order (MCO) beginning mid-March 2020. In this paper, we explore how citizens in Malaysia respond to such crises by examining letters that were submitted during the MCO period to The Star Online – the nation’s leading English online news portal. Using corpus linguistics techniques, 227 letters were firstly investigated for recurrent words/phrases used on how people talk about issues during this time. A critical discourse analysis on these recurring patterns of language was then employed to further examine their occurrences in this corpus, following Carvalho’s (2008) analysis of media discourse. This, we contend as being the synergy between corpus methods and classic CDA that contribute to the corpus-assisted discourse analysis (CADS) approach. Results yield Malaysians’ view on the matter that could describe in so far as how the country is coping with the pandemic at the time. More specifically, letters that have mostly referred to COVID-19 pandemic as being a challenge and associating it with negative expressions are in fact emotionally charged, revealing how public letters written by citizen journalists provide a much more comprehensive view of public stance on COVID-19 in Malaysia.